128k views
0 votes
Solve for u. Enter your answer in the answer box and then click Check Answer.

Solve for u. Enter your answer in the answer box and then click Check Answer.-example-1

1 Answer

6 votes

Given that:


G=(d)/(1-u)

- we cross multiply as follows:


G*(1-u)=d

- we divide both sides by G, as follows:


\begin{gathered} (G*(1-u))/(G)=(d)/(G) \\ \end{gathered}
1-u=(d)/(G)

- Subtract 1 from both sides of the equation:


1-u-1=(d)/(G)-1
-u=(d)/(G)-1

- multiply both sides of the equation by -1, as follows:


-u*-1=((d)/(G)-1)*-1
u=-(d)/(G)+1

Therefore, we have that:


u=1-(d)/(G)

or:


u=(G-d)/(G)

User Sidverma
by
5.2k points